KELEMBAGAAN BADAN USAHA MILIK DESA (BUMDES) DAN PENGARUHNYA TERHADAP KEMISKINAN RUMAH TANGGA DI KABUPATEN DONGGALA PADA MASA PANDEMI COVID-19 - Damayanti, Lien; Mukhlis, Mukhlis; Abd. Rauf, Rustam; Erny, Erny; Alamsyar, Al; R. Malik, Shintami; M. Fauzi, Disson (Politeknik Negeri Lampung., 2024)
Poverty alleviation and reduction must be done through development programs, one of which is through BUMDes empowerment. The existence of BUMDes is directed at community development policies aimed at overcoming poverty in the community. This research aims to determine the institutional effect of village-owned enterprises (bumdes) on household poverty in donggala district during the co-19 pandemic. This research was conducted in Donggala Regency, Sulawesi Province The method of determining the research location was carried out deliberately. The data analysis used in this research is qualitative analysis and quantitative analysis. The results showed that in real terms the variables of income, consumption expenditure, the presence of BUMDes and the influence of Covid-19, had an effect on household poverty in Donggala Regency. The variables of age and number of household members have no effect on poverty. Keywords:, BUMDes, Poverty, Covid 19